Improvement of Biology Learning Interest on High School Cross-Interest Program by Rangkapantas (Journal of Biology Education, 2022)
The purpose of this study was to determine the extent to which the effectiveness and efficiency of learning using the innovative teaching aid "RANGKAPANTAS", could increase student interest and learning outcomes in class XI IPS 2 in 2021/2022 semester 2 of SMAN 1 Temanggung, increase teacher professionalism in learning the concept of the Sub-Motion System. Framework concept. This research was carried out in 2 cycles, each cycle having 3 meetings. The research subject is increasing interest and learning outcomes of students in class XI-IPS 2 2021/2022 semester 2 . Student activity towards learning biology concept of motion increased by 18% from KA to Cycle I and 11.85% from Cycle I to Cycle II. That is, from activities in PBM K A 68.44%, PBM Cycle I rose to 74.59% and rose to 86.44% in PBM Cycle II. shows that students' interest in Biology subjects has increased.